Tics in Asperger's Syndrome and Autistic Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Twelve patients (8 male and 4 female; ages 3 to 32 years; 9 less than 16 years) with autistic spectrum disorder were evaluated in a Movement Disorders Clinic for tics, at the University of California, Irvine, CA.